Facile Synthesis of Au Nanoparticles Embedded in an Ultrathin Hollow Graphene Nanoshell with Robust Catalytic Performance. Issue 38 (17th August 2015) - Liu, Hongyang; Wang, Jia; Feng, Zhenbao; Lin, Yangming; Zhang, Liyun; Su, Dangsheng
<x xml:space="preserve">Abstract</x> Au nanoparticles (NPs) uniformly embedded into an ultrathin hollow graphene nanoshell (Au@HGN) are synthesized using a facile template‐based procedure. The obtained Au@HGN catalyst exhibits robust and stable catalytic performance in the reduction of 4‐nitrophenol to 4‐aminophenol, compared with that of traditional Au/TiO2 and previously reported Au‐ and Ag‐based catalysts.